Sustainable Community Development Step 2: Conduct a Community Assessment - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document explains why it is important to conduct a community assessment during a sustainability project as well as gives guidelines and suggestions about where to obtain needed information. This document is FCS7215-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.